2011
DOI: 10.1111/j.1745-6592.2011.01361.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Resistivity Imaging of a Permanganate Injection During In Situ Treatment of RDX‐Contaminated Groundwater

Abstract: Groundwater beneath the former Nebraska Ordnance Plant (NOP) is contaminated with the explosive hexahydro‐1,3,5‐trinitro‐1,3,5‐triazine (RDX) and trichloroethene (TCE). Previous treatability experiments confirmed that permanganate could mineralize RDX in NOP aquifer material. The objective of this study was to determine the efficacy of permanganate to transform RDX in the field by monitoring a pilot‐scale in situ chemical oxidation (ISCO) demonstration. In this demonstration, electrical resistivity imaging (ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Additional data were trimmed from A c c e p t e d M a n u s c r i p t 7 the data during the inversion process. The HF method has been utilized successfully within a number of applications published in the peer-reviewed literature (Halihan et al, 2005;Ong et al, 2010;Heeren et al, 2010;Heeren et al, 2011;Keppel et al, 2011;Halihan et al, 2011;Halihan et al, 2012;Christenson et al, 2012;Halihan et al, 2013;Heeren et al, 2014). Miller et al (2014) also demonstrated that the HF method was more suitable for the gravel-dominated alluvial floodplains investigated in this study by comparing the technique to the standard dipoledipole ER array and inversion.…”
Section: Electrical Resistivity Imagingmentioning
confidence: 68%
“…Additional data were trimmed from A c c e p t e d M a n u s c r i p t 7 the data during the inversion process. The HF method has been utilized successfully within a number of applications published in the peer-reviewed literature (Halihan et al, 2005;Ong et al, 2010;Heeren et al, 2010;Heeren et al, 2011;Keppel et al, 2011;Halihan et al, 2011;Halihan et al, 2012;Christenson et al, 2012;Halihan et al, 2013;Heeren et al, 2014). Miller et al (2014) also demonstrated that the HF method was more suitable for the gravel-dominated alluvial floodplains investigated in this study by comparing the technique to the standard dipoledipole ER array and inversion.…”
Section: Electrical Resistivity Imagingmentioning
confidence: 68%
“…ERI measurements were also taken at later dates (i.e., 30, 60, and 90 d), but these readings failed to conclusively locate permanganate-treated groundwater. Additional ERI details and results from this study are provided in Halihan et al (2009).…”
Section: Electrical Resistivity Imaging Of Permanganate Injectionmentioning
confidence: 99%
“…The data acquisition and inversion utilized a proprietary Oklahoma State University method (HF, OSU Office of Intellectual Property, 2004;Halihan et al, 2005) to acquire apparent resistivity data and convert them to a model resistivity profile. The HF method has been utilized successfully within a number of applications published in the peer-reviewed literature (Halihan et al, 2005;Ong et al, 2010;Heeren et al, 2010Heeren et al, , 2011Keppel et al, 2011;Halihan et al, 2011Halihan et al, , 2012Halihan et al, , 2013Christenson et al, 2012;Heeren et al, 2014). The method has even been used and accepted by government agencies, such as the Department of Defense and U.S. EPA.…”
Section: Electrical Resistivity Imaging (Eri)mentioning
confidence: 99%